"Here is the exceptional:" social media sharing and unavailable everydayness. Issue 2 (3rd April 2022) - Suetzl, Wolfgang
ABSTRACT: While social media sharing has been of great interest to communication scholarship, understanding sharing theoretically has been complicated by its everyday nature and the consequent difficulty of representing it in objectifying terms. To overcome the difficulty of defaulting into a conceptual framework that represents sharing as exchange, I employ a critical phenomenological approach to sharing that emphasizes its everydayness and problematizes the subjectivity of sharers. Drawing on Heidegger, Lefebvre, Blanchot, and de Certeau, I discuss the problem of everydayness as it presents itself in the media's straddling of the exceptional and the everyday.